Attitudefor selecting a University and Workplace for high school student : A case study of students who joined and who did not join Open day - สิงห์วีรธรรม, นภชา; เนาว์สุวรรณ, กิตติพร; ผ่องศิริ, ปัทมา; มุ่งสิน, สอาด; บุญเทียม, นภัทร (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
The survey aims to identify factors that influence high students’ choice of universityand how they choose a place ofemployment place after graduating. The research was performed using a questionnaire to collect primary data. Questions focused onhow students choose a place to study and their workplace after graduating. 632 participants were random sampingfrom students who joined and who did not join open day at Boromarajonani College of Nursing Sanpasithiprasong. The Cronbach’ Alpha Coefficient was 0.73 and the IOC was 0.67-100, both tests were employed to check the internal reliability of the evaluation. Data was analyzed though the use of descriptive statistics and Independent t-test. The results of this survey show that students who joined and not joinedthe open day were designed to choosing their university depended on the subject of their interest, family income and select based on parent suggestion. Both group of high school students selected their work place depended on their lifestyle, career part and a job that related on their subject. Moreover, open day activities significantly influence a student decision in choosinga work place near theirparents’ home town (p=<0.001). Open days are one method ofhigher education marketing. This activity allows studentsto gain a deeper understanding of an institution, on a personal level, and helps them form a more realistic impression of the school.Moreover, open dayscan improve the overall brand image of the college.